Circumferential wires as a supplement to intramedullary nailing in unstable trochanteric hip fractures: 4 reoperations in 60 patients followed for 1 year - Ban, Ilija (Informa Healthcare, 2012)
BACKGROUND AND PURPOSE: Fixation of unstable trochanteric fractures is challenging. Application of a circumferential wire may facilitate bone contact and avoid postoperative fracture displacement. However, the use of circumferential wires remains controversial due to possible disturbance of the blood supply to the underlying bone. We evaluated the results of applied circumferential wires, concentrating mainly on complications and reoperations. PATIENTS AND METHODS: 60 patients with unstable trochanteric fractures and use of circumferential wires (1 or more) and an intramedullary nail were included from 2 centers. We retrospectively assessed complications and reoperation rates within the first postoperative year. RESULTS: In 37 of the 60 patients, 2 or more circumferential wires were used. Anatomic reduction was achieved in 24 of the patients and a total cortical displacement of ≤ 10 mm was achieved in 26 other patients. 6 of the 43 patients with radiographic audit after 12 weeks sustained a subsequent fracture displacement of more than 5 mm. 4 patients underwent reoperation: 1 due to deep infection, 1 due to technical failure during osteosynthesis, 1 had a screw cut out, and 1 sustained a new fracture following a new fall. INTERPRETATION: Application of circumferential wires as a supplement to intramedullary nails in unstable trochanteric fractures is an option as it provides good primary reduction which, in most patients, is maintained over time—with no apparent increase in reoperation rate. Based on our results and on other reports, the use of circumferential wires does not appear to be harmful as sometimes claimed.